Development of a National Academic Boot Camp to Improve Fellowship Readiness - Drake, Matthew G. (ATS Sch, 2020)
Background: Pulmonary and critical care medicine (PCCM) fellowship requires a high degree of medical knowledge and procedural competency. Gaps in fellowship readiness can result in significant trainee anxiety related to starting fellowship training. Objective: To improve fellowship readiness and alleviate anxiety for PCCM-bound trainees by improving confidence in procedural skills and cognitive domains. Methods: Medical educators within the American Thoracic Society developed a national resident boot camp (RBC) to provide an immersive, experiential training program for physicians entering PCCM fellowships. The RBC curriculum is a 2-day course designed to build procedural skills, medical knowledge, and clinical confidence through high-fidelity simulation and active learning methodology. Separate programs for adult and pediatric providers run concurrently to provide unique training objectives targeted to their learners’ needs. Trainee assessments include multiple-choice pre- and post-RBC knowledge tests and confidence assessments, which are scored on a four-point Likert scale, for specific PCCM-related procedural and cognitive skills. Learners also evaluate course material and educator effectiveness, which guide modifications of future RBC programs and provide feedback for individual educators, respectively. Results: The American Thoracic Society RBC was implemented in 2014 and has grown annually to include 132 trainees and more than 100 faculty members. Mean knowledge test scores for participants in the 2019 RBC adult program increased from 55% (±14% SD) on the pretest to 72% (±11% SD; P < 0.001) after RBC completion. Similarly, mean pretest scores for pediatric course attendees increased from 54% (±13% SD) to 62% (±19% SD; P = 0.17). Specific content domains that improved by 10% or more between pre- and posttests included airway management, bronchoscopy, pulmonary function testing, and code management for adult course participants, and airway management, pulmonary function testing, and extracorporeal membrane oxygenation for pediatric course participants. Trainee confidence also significantly improved across all procedural and cognitive domains for adult trainees and in 10 of 11 domains for pediatric course attendees. Course content for the 2019 RBC was overwhelmingly rated as “on target” for the level of learner, with <4% of respondents indicating any specific session was “much too basic” or “much too advanced.” Conclusion: RBC participation improved PCCM-bound trainee knowledge, procedural familiarity, and confidence. Refinement of the RBC curriculum over the past 7 years has been guided by educator and course evaluations, with the ongoing goal of meeting the evolving educational needs of rising PCCM trainees.